DIRECT HEAT ENERGY CONVERSION INTO ELECTRICAL ENERGY: AN EXPERIMENTAL STUDY - Yezhov, Vladimir (Journal of Applied Engineering Science, 2015)
The paper presents some results of experimental studies of the co-generation of heat and electric energy in the process of an injection gas burner operation due to thermoelectric effect utilization. It also contains a description of the used laboratory installation and presents experiment methods. The authors prove the possibility to use consumer gas burners for electricity generation.